Chemical profile, antimicrobial activity, and leaf anatomy of Adenophyllum porophyllum var. cancellatum - Aguilar-Rodríguez, Silvia; López-Villafranco, Ma. Edith; Jácquez-Ríos, María Patricia; Hernández-Delgado, Claudia Tzasna; Mata-Pimentel, María Fernanda; Estrella-Parra, Edgar Antonio; Espinosa-González, Adriana Montserrat; Nolasco-Ontiveros, Erick; Avila-Acevedo, José Guillermo; García-Bores, Ana María (Frontiers in Pharmacology, 2022)
Adenophyllum porophyllum var. cancellatum, known as “árnica del monte” in Mexico, is an aromatic annual plant belonging to the Asteraceae family that grows from southern Arizona to central Mexico. The aerial parts of the plant are used in traditional medicine to treat skin diseases such as irritations, infections, and wounds. In this study, the essential oil of this plant was characterized, and its antimicrobial activity was evaluated. This species has large glands in its leaves; therefore, for quality control purposes, an anatomical study of the leaves was performed. The essential oil was isolated from the aerial parts of the plant through hydro-distillation and analyzed using a gas chromatography/ mass spectrometry (GC/MS) system. Its anti-yeast activity was evaluated against three Candida species and ten bacterial strains using the disk diffusion technique. The minimum inhibitory concentration (MIC), minimum fungicidal concentration (MFC), and minimum bactericidal concentration (MBC) were determined using broth microdilution. Anatomical study was performed on the middle part of the leaf. A yield of 0.5 % of the essential oil was obtained from the herb, and Eighteen compounds in the essential oil were identified, within them trans pinocamphone (29.5 %), limonene (24.7 %), pinocarvone (21.8 %), and cis pinocamphone (8.0 %) were the main components. The inhibition zones were between 10 mm and 20 mm, and the MIC and MFC against the three Candida species ranged from 60 µg/mL to 500 µg/mL. The leaf anatomy showed anisocytic stomata, simple and glandular trichomes of different types, and large and elliptical-shaped lysigenous glands, which can be used for taxonomic identification. The A. porophyllum var. cancellatum essential oil can serve as an alternative source of natural antimicrobial agents as an affordable approach to control infectious diseases. This is the first study that reports the chemical composition and antimicrobial activity of the essential oil, as well as the leaf anatomy of this species.